Transdermal Drug Delivery - Tan, Zi Hui (2014)
Sonophoresis is the use of ultrasound to transport medicinal agents through the skin. With sonophoresis, absorption of drugs into the skin is exponentially increases. Due to the ultrasound waves, the skin is stimulated by micro-vibrations, escalating the overall kinetic energy of formulating molecules of these agents. During sonophoresis, holes are created in the skin allowing fluid to enter the human body – acoustic waves disturb the lipid bilayers. With the use of ultrasound, drug delivery is improved by cavitation, microstreaming, and heating. For this study, the main objective is to understand the influence of frequency of ultrasound used on Transdermal Drug Delivery (TDD) systems and damage to the skin. Principally, an increase in skin permeability should not be in the expense of permanent damage to the skin. In the study, two ultrasound transducers of frequencies 200kHz and 1MHz respectively was fabricated and calibrated. To study the effects of frequency of ultrasound on effectiveness of fluorescent nanoparticles penetration through porcine ear skin, microplate readings of fluorescent intensity before and after sonication were obtained. Subsequently, Scanning Electron Microscope (SEM) imaging of porcine samples were also taken for visualization of possible damages made to the skin. To isolate the effects of varying frequency in TDD systems, 60nm fluorescent nanoparticles was used at a fixed intensity of 1.5W/cm2, with sonication exposure time of 15 minutes. For better appreciation of results, a list of topics was reviewed – benefits and limitations of TDD systems, sonophoresis and effects of frequency on its efficacy, piezoelectric effects and efficiency of a matching network box. Overall results was analysed and compared, and it was found that the lower frequency transducer (200kHz) causes more biological effects, while the higher frequency transducer (1MHz) has higher efficacy in drug penetration.